BETEKHTINITE FROM THE UDOKAN SANDSTONE-HOSTED COPPER DEPOSIT (TRANSBAIKALIA, RUSSIA) - K.A. Novoselov; E.V. Belogub; V.A. Kotlyarov; V.V. Schilovskikh (Минералогия)
The paper describes betekhtinite from the Udokan sandstone-hosted copper deposit for the first time, which is a rare mineral of the chalcocite-bornite ores. The mineral assemblage of betekhtinite indicates its low-temperature origin. The mineral contains up to 2.1 wt. % Ag and variable Fe amount. The sulfur deficiency of betekhtinite is probably related to its partial alteration.